Analysis of Energy Supply Substitution from a Diesel Power Plant System to a Solar Power Plant System Based on Capacity Design for the Office Load of PT XYZ in Karimun Regency, Indonesia - Muhammad Iqbal; Andre Kurniawan; Arwizet K; Yolli Fernanda (Jurnal Vokasi Mekanika (VoMek), 2026)
The dependence of the office load at PT XYZ on Diesel Power Plants (DPPs) in a mini-grid electricity system creates the need for an alternative energy supply that is more efficient, reliable, and compatible with local solar potential. The present study aims to design and analyze the performance of a battery-based off-grid Solar Photovoltaic Power Plant (SPP) to independently supply office electricity demand by considering the load profile, photovoltaic module configuration, controller/MPPT converter, battery capacity, module orientation, and system losses. The method consists of daily load profile analysis, the use of Meteonorm meteorological data for the Sungailimau site, fixed module orientation with a tilt angle of 5° and an azimuth of 0°, and stand-alone system simulation using PVsyst V8.1.2. The proposed system consists of 200 Longi Solar modules rated at 560 Wp, with a total installed capacity of 112 kWp, The solar power system is designed in a modular configuration consisting of 4 PV blocks. Each block consists of 5 strings connected in parallel, with each string comprising 10 PV modules connected in series. The total system configuration consists of 20 strings., an MPPT converter-based controller, and a BYD Box Premium HVM 22.1 lithium-ion LFP battery storage system with 368,6 kWh of stored energy. The simulation results show 105.989 kWh/year of useful solar energy, 151.191 kWh/year of available solar energy, 49.213 kWh/year of unused energy, a performance ratio of 56,64%, a solar fraction of approximately 92,33%, and 1.856 kWh/year missing energy.